Impact of Public Policies and Initiatives on Corporate Social Responsibility of Healthcare Institutions - Al-marshad, Sultan O.; Kilase Ajoud, Mohamed Eid (European Journal of Sustainable Development, 2024)
The present study aims to examines the impact of public policies and initiatives on corporate social responsibility of the healthcare institutions working in the Northern Border Regions of Saudi Arabia. The study used descriptive and analytical methodology. The questionnaire was designed, and distributed to the random sample of 300 members of the staff chosen from the healthcare institutions including public hospitals, private hospitals and health centers. The descriptive statistics results showed that all variables of the study are characterized by a mean value higher than 3. Moreover, results showed that all the variables of the public policies and initiatives have a statistically significant effect on the environment indicators of corporate social responsibility. On the hand, the legal framework and the capacity building have positive effect on the CSR however, integrating activities impact the environment indicators of social responsibility negatively. Keywords: Public Policies, Corporate Social Responsibility, governance, initiatives, integrating activities